Disruption, values and resilience: The British Library's response to the Covid-19 pandemic. Issue 2 (August 2020) - Keating, Roly
This article focuses on the institutional response of the British Library to the Covid-19 pandemic over the course of the past year. National libraries have a key part to play as the world recovers, and the experiences of the British Library highlight the central role of digital in adapting to massive disruption, of the importance of institutional values in steering a course through a year of crisis, and the contribution that we can make to building national and international resilience against future shocks and turmoil.